The future of American jails: a national survey of jail leaders' ideals - Applegate, Brandon K. (The prison journal, 2024)
Despite their significance in criminal legal processing, American jails have a reputation for physical and operational deficiencies, with few aspirations beyond mere custody. To examine the possibilities for United States (U.S.) jails’ progress, we assess the priorities of U.S. jail leaders, their expectations about achieving reforms, and perceived obstacles regarding change. Our analysis showed that while jail command staff embrace custody, they also endorse social service functions of jails, favor facilities that are safe and clean, support a professional workforce, accept other progressive features of jails, and reject punishment and brutality. They recognize impediments to progress, but are optimistic about potential improvements.